A review of multi-criteria assessment of the social sustainability of infrastructures. (20th June 2018) - Sierra, Leonardo A.; Yepes, Víctor; Pellicer, Eugenio
Abstract: Nowadays multi-criteria methods enable non-monetary aspects to be incorporated into the assessment of infrastructure sustainability. Yet evaluation of the social aspects is still neglected and the multi-criteria assessment of these social aspects is still an emerging topic. Therefore, the aim of this article is to review the current state of multi-criteria infrastructure assessment studies that include social aspects. The review includes an analysis of the social criteria, participation and assessment methods. The results identify mobility and access, safety and local development among the most frequent criteria. The Analytic Hierarchy Process and Simple Additive Weighting methods are the most frequently used. Treatments of equity, uncertainty, learning and consideration of the context, however, are not properly analyzed yet. Anyway, the methods for implementing the evaluation must guarantee the social effect on the result, improvement of the representation of the social context and techniques to facilitate the evaluation in the absence of information. Highlights: Review of multi-criteria assessment methods of infrastructure social sustainability. Identify trends of social criteria considered. Identify trends of participation of stakeholders. Identify trends of multi-criteria methods. Identify trends of consideration of equity, context and social learning.